ENHANCING ROAD SAFETY: RECOMMENDATIONS FOR DEVELOPMENT AND IMPLEMENTATION - Khodjayev Sanjar Muhammedovich (Web of Journals Publishing, 2024)
This article invsetigates a scheme for studying pedestrian traffic has been developed to develop recommendations for the rational placement of pedestrian crossings, the order of movement of cars on city streets, the improvement of road infrastructure, the legal culture of traffic participants, and traffic safety. 'provision studied. At the same time, to avoid various road traffic accidents, the issues of increasing the efficiency of the car drivers in the process of transporting passengers and the behavior of pedestrians were analyzed. In addition, it was recommended to improve the legal criteria for bringing pedestrians to administrative responsibility for violating traffic rules and to create an electronic system for the immediate formalization and review of materials on administrative violations in the field of traffic.
Keywords: Infrastructure, car traffic, pedestrian traffic, electronic system, traffic participants, violations, traffic lights, highway, traffic flow.